Physiological And Psychological Development Of Children From 6 To 7 Years Old In Preschool Education - Nigora Xidoyatova (Euro Asian Journal Publishing, 2024)
Currently, in Uzbekistan, the problem of preschool education has acquired priority significance, as evidenced by a number of state regulations and regulatory documents, which pay special attention to the fact that "preschool education is an integral process aimed at ensuring the comprehensive development of a preschool child in accordance with his or her inclinations, inclinations, individual psychological and physical characteristics, the formation of moral standards in the child, the acquisition of life and social experience.
Keywords: preschool education; child psychology; physical development